2015
DOI: 10.1016/j.toxrep.2015.06.010
|View full text |Cite
|
Sign up to set email alerts
|

Protective effects of novel organic selenium compounds against oxidative stress in the nematode Caenorhabditis elegans

Abstract: HighlightsNovel organic selenium compounds presented low toxicity over C. elegans survival.Defecation cycles were decreased by Novel organic selenium compounds, except C1.Novel organic selenium compounds, except C1 decreased AChE enzyme activity.All compounds tested prevented from juglone stress.C2 selenium compound decreased GST-4::GFP fluorescence under juglone stress.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
13
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 29 publications
(17 citation statements)
references
References 34 publications
4
13
0
Order By: Relevance
“…Several studies have shown that antioxidant therapies attenuate the tissue damage caused by oxidative stress . In this regard, we designed our study following previous results from our lab showing that β‐selenoamines presented significant antioxidant properties in vitro and in a Caenorhabditis elegans model …”
Section: Discussionsupporting
confidence: 51%
See 2 more Smart Citations
“…Several studies have shown that antioxidant therapies attenuate the tissue damage caused by oxidative stress . In this regard, we designed our study following previous results from our lab showing that β‐selenoamines presented significant antioxidant properties in vitro and in a Caenorhabditis elegans model …”
Section: Discussionsupporting
confidence: 51%
“…We also verify that treatment with β‐selenoamines decreases both measures, indicating that C1 and C2 save the liver against TAA‐induced oxidative stress. Our previous studies have shown that β‐selenoamines exert significant antioxidant activity against Fe(II) and sodium nitroprusside‐induced lipid peroxidation in vitro , as well as protect Caenorhabditis elegans against juglone‐induced toxicity by selenol groups formation …”
Section: Discussionmentioning
confidence: 56%
See 1 more Smart Citation
“…Oxidative stress is considered a major factor in many pathophysiologies of various diseases and aging , and results from excessive generation of reactive oxygen species or a decline in antioxidative defenses systems . Several studies have shown that trace amounts of inorganic selenite and organic selenium compounds such as modified diphenyl diselenide have abilities to decrease oxidative stress generation . In this study, we used a novel form of organic selenium, Glu‐SeMet, which was modified from selenomethionine.…”
Section: Resultsmentioning
confidence: 99%
“…C. elegans has only one selenoenzyme (TrxR-1) compared to the 25 in humans, 2628 deletion of this gene has not been observed to alter Se toxicity in C. elegans , 29 and low levels of Se stimulate nematode growth 21, 30 and are protective against oxidative stress in C. elegans . 3134 Our objective was to measure growth impacts from multiple combinations of inorganic and organic forms of Hg and Se and, in doing so, examine the importance of (1) Se compound and concentration, (2) Se/Hg molar ratio of the exposure medium, and (3) internal Se/Hg molar ratio to toxicity recovery.…”
Section: Introductionmentioning
confidence: 99%